KAJIAN EMPIRIS FINANCIAL RESTATEMENTS AKIBAT PERUBAHAN STANDAR AKUNTANSI KEUANGAN DI INDONESIA - Wulanditya, Putri (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
Changes in accounting standards make listed companies comply with these provisions. As a result of the adoption of a new or revised PSAK, companies make a restatement of financial statements. This study aims to determine the facts of the restatement of the financial statements of public companies in Indonesia. The research method used is descriptive quantitative by analyzing the financial reports and notes on the audited financial statements. The results of this study indicate that 69 percent of companies make a restatement of financial statements. The sequence of sectors that carried out the most restatements was (1) the basic industry & chemical sector, (2) the consumer goods industry sector, then (3) the agriculture sector. The majority of restatements of financial statements occurred in 2015 and 2018 with PSAK 24, PSAK 69 and reclassification as the main causes. This research has implications for users of financial statements to pay attention to the impact of changes in accounting standards that may be taken into consideration in making decisions.